Therapeutic Targeting of Endosome and Mitochondrial Reactive Oxygen Species Protects Mice From Influenza Virus Morbidity - To, Eunice E.; Erlich, Jonathan R.; Liong, Felicia; Liong, Stella; Luong, Raymond; Oseghale, Osezua; Miles, Mark A.; Papagianis, Paris C.; Quinn, Kylie M.; Bozinovski, Steven; Vlahos, Ross; Brooks, Robert D.; et al. (Frontiers in Pharmacology, 2022)
There is an urgent need to develop effective therapeutic strategies including immunomodulators to combat influenza A virus (IAV) infection. Influenza A viruses increase ROS production, which suppress anti-viral responses and contribute to pathological inflammation and morbidity. Two major cellular sites of ROS production are endosomes via the NOX2-oxidase enzyme and the electron transport chain in mitochondria. Here we examined the effect of administration of Cgp91ds-TAT, an endosome-targeted NOX2 oxidase inhibitor, in combination with mitoTEMPO, a mitochondrial ROS scavenger and compared it to monotherapy treatment during an established IAV infection. Mice were infected with IAV (Hkx31 strain; 104PFU/mouse) and 24 h post infection were treated with Cgp91ds-TAT (0.2 mg/kg), mitoTEMPO (100 μg) or with a combination of these inhibitors [Cgp91ds-TAT (0.2 mg/kg)/mitoTEMPO (100 μg)] intranasally every day for up to 2 days post infection (pi). Mice were euthanized on Days 3 or 6 post infection for analyses of disease severity. A combination of Cgp91ds-TAT and mitoTEMPO treatment was more effective than the ROS inhibitors alone at reducing airway and neutrophilic inflammation, bodyweight loss, lung oedema and improved the lung pathology with a reduction in alveolitis following IAV infection. Dual ROS inhibition also caused a significant elevation in Type I IFN expression at the early phase of infection (day 3 pi), however, this response was suppressed at the later phase of infection (day 6 pi). Furthermore, combined treatment with Cgp91ds-TAT and mitoTEMPO resulted in an increase in IAV-specific CD8+ T cells in the lungs. In conclusion, this study demonstrates that the reduction of ROS production in two major subcellular sites, i.e. endosomes and mitochondria, by intranasal delivery of a combination of Cgp91ds-TAT and mitoTEMPO, suppresses the severity of influenza infection and highlights a novel immunomodulatory approach for IAV disease management.